Wainman Shows the Way - Zhang, Jack (The Meducator, 2016)
Dr. Bruce Wainman is an associate professor of Pathology and Molecular Medicine at McMaster University. He is also the division director of Anatomy and the current director for the Education Program in Anatomy. Additionally, Dr. Wainman serves as the coordinator for biological sciences for the Ontario Midwifery Consortium. He teaches Pharmacology, Anatomy and Physiology, and Reproductive Physiology at McMaster University. In February 2016, Dr. Wainman was awarded the 3M National Teaching Fellowship – Canada’s most prestigious undergraduate teaching award. Dr. Wainman’s current research interest includes how environmental contaminants impact human reproductive health. Specifically, Dr. Wainman aims to identify the relationship between exposure to environmental contaminants and the alteration in menstrual cycle function. Dr. Wainman obtained his undergraduate degree in biochemistry from Laurentian University, a Master’s Degree in Medical Sciences from McMaster University, and a PhD in biology from York University.